2004
DOI: 10.1158/1078-0432.ccr-04-0002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Sequential Chemotherapy in Advanced Non-Small Cell Lung Cancer (SWOG 9806)

Abstract: Purpose: Improving chemotherapeutic efficacy in nonsmall cell lung cancer (NSCLC) will require the development of new drugs or new strategies to better use currently available agents. Sequential administration offers an opportunity to increase drug diversity while maintaining dose intensity. On the basis of the data indicating the activity of taxanes as second-line therapy and the lack of efficacy for more than three cycles of platinum-based therapy, this randomized Phase II study tested the concept of planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Recently, Edelman et al (2001a) reported the results of phase II study for sequential combination chemotherapy consisting of carboplatin and GEM followed by paclitaxel showed modest activity (overall response: 31%, median survival time: 9.5 months). Based on the results of this study, Southwest Oncology Group (SWOG) has completed a randomised phase II trial of two sequential combinations (CDDP/VNR followed by DOC vs carboplatin/GEM followed by paclitaxel) and reported that both arms had comparable activity (response rate: 21 and 28%, 1-year survival: 32 and 31%) (Edelman et al, 2001b). The concept of this SWOG study which involved a doublet followed by taxane, is similar to that of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Edelman et al (2001a) reported the results of phase II study for sequential combination chemotherapy consisting of carboplatin and GEM followed by paclitaxel showed modest activity (overall response: 31%, median survival time: 9.5 months). Based on the results of this study, Southwest Oncology Group (SWOG) has completed a randomised phase II trial of two sequential combinations (CDDP/VNR followed by DOC vs carboplatin/GEM followed by paclitaxel) and reported that both arms had comparable activity (response rate: 21 and 28%, 1-year survival: 32 and 31%) (Edelman et al, 2001b). The concept of this SWOG study which involved a doublet followed by taxane, is similar to that of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy with platinum-based regimens for more than 6 cycles was usually considered unendurable (Edelman et al, 2004;Belani et al, 2006). However, in our study, we found that the myelosuppression toxicity remained generally tolerable during the whole treatment with G-CSF support.…”
Section: Discussionmentioning
confidence: 48%
“…Two phase II trials have been published on sequential chemotherapy (table 10) [94,95]. The ELCWP completed a large phase III trial [95] where patients without disease progression after three courses of cisplatin-based chemotherapy were randomised between further platinum-based chemotherapy or paclitaxel with crossover at the time of progression.…”
Section: Sequential Chemotherapymentioning
confidence: 99%